DARI TRADISIONAL KE DIGITAL: ADOPSI MEDIA SOSIAL DALAM PERDAGANGAN HASIL BUDIDAYA IKAN PADA MASA PANDEMI DI KOTA PALANGKA RAYA - Wahyuni, Muhammad (Likuid Jurnal Ekonomi Industri Halal, 2021)
he purpose of this study is to describe specifically the related reality of traditional to digital trade: the adoption of social media in the trade of fish cultivation during the Pandemic in palangka raya city. Fish harvests and fish catches in the Kahayan river usually people sell them in the market and offer to the surrounding residents through traditional buying and selling, when the pandemic makes people turn to digital transactions. Digital media that is often used is Facebook and Whatsapp media as a promotional tool as well as a digital buying and selling tool conducted by fish farmers. This study uses qualitative method with phenomenological approach. Data is collected through three ways, namely observation, interview, and documentary studies. This research found that traditional to digital trade: the adoption of social media in the trade of fish cultivation during the Pandemic in palangka raya city, where social media is quite effective as a tool to develop income from sales on social media, especially in the trading activities of fish cultivation.Keywords: Transactions, digital transactions and fish farming products